Cardiovascular safety and efficacy of metformin-SGLT2i versus metformin-sulfonylureas in type 2 diabetes: systematic review and meta-analysis of randomized controlled trials - Desye Gebrie (Nature Portfolio, 2021)
Abstract Diabetes is a serious threat to global health and among the top 10 causes of death, with nearly half a billion people living with it worldwide. Treating patients with diabetes tend to become more challenging due to the progressive nature of the disease. The role and benefits of combination therapies for the management of type 2 diabetes are well-documented, while the comparative safety and efficacy among the different combination options have not been elucidated. We aimed to systematically synthesize the evidence on the comparative cardiovascular safety and efficacy of combination therapy with metformin-sodium-glucose cotransporter-2 inhibitors versus metformin-sulfonylureas in patients with type 2 diabetes. We searched MEDLINE-PubMed, Embase, Cochrane Library, and ClinicalTrials.gov up to 15 August 2019 without restriction in the year of publication. We included randomized controlled trials of patients with type 2 diabetes who were on metformin-sodium-glucose cotransporter-2 inhibitors or metformin-sulphonylureas combination therapy at least for a year. The primary endpoints were all-cause mortality and serious adverse events, and the secondary endpoints were cardiovascular mortality, non-fatal myocardial infarction, non-fatal stroke, hypoglycemia, and changes in glycated hemoglobin A1c (HbA1c), body weight, fasting plasma glucose, blood pressure, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol. We used a random-effects meta-analysis model to estimate mean differences for continuous outcomes and risk ratio for dichotomous outcomes. We followed PICOS description model for defining eligibility and the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) 2015 guidelines for reporting results. Of 3,190 citations, we included nine trials involving 10,974 participants. The pooled analysis showed no significant difference in all-cause mortality (risk ration [RR] = 0.93, 95% CI [0.52, 1.67]), serious adverse events (RR = 0.96, 95% CI [0.79, 1.17]) and adverse events (RR = 1.00, 95% CI [0.99, 1.02]) between the two, but in hypoglycemia (RR = 0.13, 95% CI [0.10, 0.17], P < 0.001). Participants taking metformin-sodium glucose cotransporter-2 inhibitors showed a significantly greater reduction in HbA1c (mean difference [MD] = − 0.10%, 95% CI [− 0.17, − 0.03], body weight (MD = − 4.57 kg, 95% CI [− 4.74, − 4.39], systolic blood pressure (MD = − 4.77 mmHg, 95% CI [− 5.39, − 4.16]), diastolic blood pressure (MD = − 2.07 mmHg, 95% CI [− 2.74, − 1.40], and fasting plasma glucose (MD = − 0.55 mmol/L, 95% CI [− 0.69, − 0.41]), p < 0.001. Combination therapy of metformin and sodium-glucose cotransporter-2 inhibitors is a safe and efficacious alternative to combination therapy of metformin and sulphonylureas for patients with type 2 diabetes who are at risk of cardiovascular comorbidity. However, there remains a need for additional long-term randomized controlled trials as available studies are very limited and heterogeneous.